Mobile Applications for Personal Financial Management in the Digital Era: A Systematic Review - Richardi, Bryan; Vílchez, Miguel; Alarcón, Felipe; León-Velarde, Cesar (LACCEI, 2024)
Abstract - The study delves into the constant evolution of technology, which has led to the proliferation of mobile financial applications and e-wallets, transforming the way individuals manage their personal finances. This study aims to explore the impact of mobile financial applications and e-wallets on personal financial management, with a focus on trust and security challenges. PICO methodologies were employed to define specific questions, and PRISMA was used for a rigorous data selection. After applying inclusion and exclusion criteria, 37 articles were identified, of which21 were relevant to the research. The results reveal common challenges, such as distrust in technological security and a lack of financial education. Asia stands out as a leader in the research and development of mobile applications, and the demographic diversity of the studies provides a comprehensive insight into financial practices. In conclusion, this study offers a comprehensive view of the adoption of financial technologies, focusing on "Financial Inclusion" as a key impact.